Film Poster Design: Understanding Film Poster Designs and the Compositional Similarities within specific genres - Sneha Pooranalingam (Spectrum, 2024)
A film poster is an integral part of the promotion and marketing of an upcoming film. It encapsulates the essence of the film and is used in theatres, DVDs, and advertisements. For effective promotion, designers must create film posters that are relevant to the film they represent. This study explored whether film posters have common compositional aspects within genres. Previous research has explored genre classification and colour theory within film posters. However, the analysis of composition within film posters has been insufficiently researched in the context of recognizing patterns throughout film genres. I explored four film genres and analyzed existing film posters within these genres using a visual analysis tool. The analysis was then used to define a summarized composition of each genre, which then created generated posters using this analysis and definition. These generated posters consisted of low fidelity posters made using basic shapes such as circles and squares. The posters were used in participant interviews which followed a semi-structured approach. I asked participants questions to further their reflection about the posters and create discussion. Each participant was asked to label each poster with a genre based on their understanding of what they would assume to be the genre of the generated film poster. After analyzing the results from the participants’ decisions, the findings indicate that film posters have similar compositions within genres. These similarities are further recognized by film consumers and impact consumers’ perceptions of film posters.